Students’ Learning Activities In Executing Policy Of Study From Home (SFH) As Response Over Covid-19 Pandemic: (Case Study: City of Serang) - Gintings, Abdorrakhman; Kusuma, Andiko Nugraha; Fathoni, N. S. (Advances in Social Sciences Research Journal, 2020)
The Covid-19 pandemic has negatively affected human life. Indonesia Government issued policy on SFH (Study from Home) to respond this situation. This research tried to find out the effectiveness of implementation of that policy on the students both in state and private Junior High Schools (SMP), Senior High Schools (SMA), and Vocational High Schools (SMK). Data was collected from the distributed closed-ended and open-ended questions to 180 students in City of Serang, Banten Province, Indonesia. The scores ranged from minimum 1.00 as Very Poor and 5.00 as Very Good. The implementation of SFH resulted Mean score 2.7911, which was in Fair category. The independent T-Test with probability value 0.05 showed that there were no differences on performances of the school groups, except between the Junior High School (SMP) and Senior High School (SMA) with Vocational High School (SMK). The dominant problems were less various learning design, non-interactive learning, too much assignment, less optimum learning on practical courses for students of Vocational School, less experienced teacher in distance learning, less assistance by parents, and cost for using social media. To sum up, distance-learning SFH was not effectively executed for there were technical problems related to the unpreparedness of the stakeholders, including the government. It is recommended that the implementation of SFH is made lesson learned as the input to design the education providence in new normal era including methods, management, and funding.